2016
DOI: 10.1051/0004-6361/201527320
|View full text |Cite
|
Sign up to set email alerts
|

Zeeman-Doppler imaging of active young solar-type stars

Abstract: Context. By studying young magnetically active late-type stars, i.e. analogues to the young Sun, we can draw conclusions on the evolution of the solar dynamo. Aims. We determine the topology of the surface magnetic field and study the relation between the magnetic field and cool photospheric spots in three young late-type stars. Methods. High-resolution spectropolarimetry of the targets was obtained with the HARPSpol instrument mounted at the ESO 3.6 m telescope. The signal-to-noise ratios of the Stokes IV mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 35 publications
11
47
0
Order By: Relevance
“…5. These continuum brightness distributions were derived using the modified Tikhonov regularisation method (see Hackman et al 2016;Rosén et al 2018), which numerically stabilises the surface imaging problem by minimising the local map contrast and limiting deviation from the default Owing to a large inclination angle, the Doppler mapping method is unable to distinguish the Northern and Southern stellar hemispheres, except when the surface features are partially obscured during the primary and secondary eclipses. This is why the recovered dark spot geometries are symmetric with respect to the stellar equators everywhere except close to 0 • longitude (phase 0.0) for YY Gem A and 180 • longitude (phase 0.5) for YY Gem B.…”
Section: Brightness Distributionmentioning
confidence: 99%
“…5. These continuum brightness distributions were derived using the modified Tikhonov regularisation method (see Hackman et al 2016;Rosén et al 2018), which numerically stabilises the surface imaging problem by minimising the local map contrast and limiting deviation from the default Owing to a large inclination angle, the Doppler mapping method is unable to distinguish the Northern and Southern stellar hemispheres, except when the surface features are partially obscured during the primary and secondary eclipses. This is why the recovered dark spot geometries are symmetric with respect to the stellar equators everywhere except close to 0 • longitude (phase 0.0) for YY Gem A and 180 • longitude (phase 0.5) for YY Gem B.…”
Section: Brightness Distributionmentioning
confidence: 99%
“…The ZDI mapping was performed with the Inver-sLSD code developed by Kochukhov et al (2014) and subsequently used for cool active stars by Rosén et al (2016), Hackman et al (2016) and Kochukhov & Lavail (2017). This code divides the stellar surface into surface elements of roughly equal area, and for each surface element, the local line profiles are computed using the Unno-Rachkovsky analytical solution of the polarised radiative transfer equations (Landi Degl'Innocenti & Landolfi 2004).…”
Section: Zeeman Doppler Imagingmentioning
confidence: 99%
“…In the Sun, the longitudinal distribution of sunspots indicates that the solar large-scale magnetic field is mostly axisymmetric (e.g., Pelt et al 2006). In late-type stars with rapid rotation, by contrast, much larger spots located at high latitudes or even polar regions have been observed using Doppler imaging (DI), Zeeman Doppler imaging (ZDI), and interferometry (e.g., Järvinen et al 2008;Hackman et al 2016;Roettenbacher et al 2016). Many studies have reported on highly nonaxisymmetric spot configurations (e.g., Jetsu 1996;Berdyugina & Tuominen 1998), referred to as active longitudes, while especially the indirect imaging of the surface magnetic field using ZDI tends to yield more axisymmetric configurations See et al 2016).…”
Section: Introductionmentioning
confidence: 99%